Getting up to Speed: Informing Prior and Prospective Blood Donors about Supply Uncertainty and Hygiene Measures during the COVID-19 Lockdown - Anne Kathrin Heynold; Michael Haylock; Stefanie Ehmann (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2022)
The already uncertain supply of whole blood from donors has been made even more volatile by the COVID-19 pandemic. Potential reasons for the persistence of this shock are unawareness of the supply drop, and fear of infection while donating. The primary aim of this study is to test efficacy of measures used by donation organizations and media to appeal to donors and nondonors to donate blood and ensure donor safety during the COVID-19 pandemic. The secondary aim is to explore why some donors donated less as a result of the pandemic. Using a survey experiment with 1,207 participants, we test the effect of informing subjects about donation urgency (shortage information), and secondly, the effect of reducing the potential fear of a SARSCoV-2 infection (hygiene information) on their inclination to donate before and after the COVID-19 lockdown ended. The results show that shortage information increases willingness to donate for prospective blood donors by 15 percentage points (pp), and increases the willingness of (prospective) donors to donate within the next month by 12pp (9pp), on average. Hygiene information reduces the intention of prior donors to donate again by 8pp, on average. The experimental results are corroborated by evidence from previous donations, showing a 12pp lower likelihood to donate less in 2020 than in 2019 for those who had been informed about shortages by donation organizations. The results suggest that interventions focusing on the marginal impact of donation are more effective than interventions focusing on marginal costs.
Keywords: D12; D64; H12; I18; 330; Blood donation; altruism; urgency; uncertainty